Environmental dimorphism of the frequency of significant correlations of the torso features with the feet features among 7-13-year-old youth - Rzadkowski, Kamil; Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2023)
Introduction. Studies on the correlation of selected torso and feet features among 7-13-year-old children and adolescents have shown that the most frequent and strongest correlations with feet features occur among girls at the age of 11 and 12 years and among boys at 11, 12 and 13 years old. Material and method. The research was carried out in the group of adolescents aged 7 to 13 and registered 16,462 observations, including 5,552 from the urban area and 10,910 from rural environment, together with 87 features describing torso and feet. The work stand for measuring selected features using the photogrammetric method consists of a computer and a card, programme, monitor, printer and a projection-receiving device with a camera. Conclusions The frequency of significant correlations of torso features with feet features that differentiate the rural environment from urban is greater, however, the urban area presents more frequent relationship with feet features at a different level. Features of the frontal and transversal plane tell the rural environment apart, whereas the urban environment is only differentiated by the frontal plane. The frequency of significant relationships of the feet features, which torso features correlate with and differentiate between the rural and urban environment is greater. Therefore, these are the morphological features that characterize the longitudinal arch of the feet. The features that differentiate the urban environment are those describing only the longitudinal arche.